O “pulso das águas” e o acesso à rede de urgência e emergência da população ribeirinha na região do baixo Amazonas/AM - (:unkn) unknown (Universidade Federal do Amazonas, 2020)
The Amazon is a unique territory and the relationships established with the environment, make the population's ways of life also different. This study sought to understand the flows and networks produced in access to health and in the production of care for the riverside population in the municipality of Barreirinha. We used cartography as a methodological approach, allowing us to map the networks established in the territory with regard to access to health. We use the tool of the user-guide to go through the points of the network produced by the users, starting from a need for assistance in urgent and emergency situations. This study showed that environmental factors such as flood, drought and the strength of the river have an influence on access to services in this region, however, these do not become barriers to access. In the high water period, the main reasons for removal are classified as "Pregnancy, Childbirth and Puerperium" while in low water the reasons "External causes of morbidity and mortality" are the main reasons. Finally, we understand that the Amazon, with its socioenvironmental characteristics, poses challenges for the development of public health policies, and point us to the need to carry out analyzes and studies so that we can follow the dynamics of the lives of people and populations on the riverside net territory
Keywords: População rural; Ciclo hidrológico; População ribeirinha; Barreirinha (Amazonas); Acesso aos serviços de saúde; CIÊNCIAS AGRÁRIAS; Acesso à saúde; Território; População rural; Ciclo hidrológico